Horticulture As an Avenue of Sustainable Agriculture in India - V. Basil Hans; Bharathraj; S. Nejar (International Journal of Trends in Horticulture, 2025)
In the face of climate change, soil degradation, and population pressure, sustainable agriculture has become a necessity for India. Within this broader framework, horticulture which includes the cultivation of fruits, vegetables, spices, plantation crops, flowers, and medicinal plants has emerged as a key pillar of sustainable agricultural practices. With its potential to ensure food and nutritional security, enhance rural livelihoods, and contribute to ecological balance, horticulture holds a strategic position in India's agricultural transformation. Horticulture has emerged as a crucial component of sustainable agriculture in India, offering a viable solution to the challenges of food security, environmental degradation, and rural livelihood development. Unlike traditional cereal-based farming, horticultural practices are resource efficient, climate-resilient, and economically rewarding, especially for small and marginal farmers. This paper explores the multifaceted role of horticulture in promoting sustainability through increased productivity, enhanced nutritional security, employment generation, and ecological balance. It also highlights key government initiatives and sustainable practices driving the sector forward. Despite challenges such as post-harvest losses and market access, horticulture presents significant potential to transform India's agricultural landscape into a more resilient and sustainable system
Keywords: Sustainable agriculture; climate resilience; horticulture; nutritional security; post-harvest management; resource efficiency; rural livelihoods